Effects of Hypoxia on Habitat Quality of Reservoir Largemouth Bass, Saugeye, and White Crappie. Issue 1 (13th January 2021) - Budnik, Richard R.; Steinhart, Geoffrey B.; Conroy, Joseph D.; Dillon, Rebecca A.; Zweifel, Richard D.; Ludsin, Stuart A.
Abstract: Hypoxia induced by eutrophication and high summer temperatures is common in most Midwestern reservoirs, with uncertain effects on resident fishes. To evaluate the potential influence of low dissolved oxygen (DO) and high‐temperature conditions on habitat quality for three common sport fishes (Largemouth Bass Micropterus salmoides, saugeye [Walleye Sander vitreus  × Sauger S. canadensis ], and White Crappie Pomoxis annularis ), we used spatially explicit bioenergetics models to measure growth rate potential (GRP) in three Ohio reservoirs of varying productivity and size. Dissolved oxygen, temperature, and prey biomass data were collected throughout each study reservoir during August in 2015 or 2016, when temperature and hypoxia levels were expected to be at or near their peak. Growth rate potential was generally low in hypoxic bottom waters and higher in the epilimnion due to prey concentrating above the oxycline. The amount of high‐quality habitat (HQH; i.e., GRP > 0 g/g/d) always declined owing to hypoxia; however, the extent of the decline depended on the modeled species and reservoir. Among species, hypoxia‐induced losses of HQH were small, differing by less than 8% in each reservoir. Among‐reservoir differences in HQH were greater; reductions in HQH ranged from 31.3% to 42.5% among species in the reservoir with the lowest DO (mean ± SE = 2.7 ± 0.04 mg/L) and highest gape‐appropriate prey biomass (5.1 ± 0.07 to 5.3 ± 0.07 g/m 3 ), whereas they varied by 0.3–0.6% in the reservoir with the highest DO (5.1 ± 0.07 mg/L) and lowest gape‐appropriate prey biomass (0.2 ± 0.004 to 0.6 ± 0.01 g/m 3 ). Even so, the reservoir with the lowest mean DO (i.e., greatest hypoxic extent) had the highest mean GRP and percentage HQH owing to high prey biomass. Collectively, our findings indicate that bottom hypoxia can reduce sport fish habitat quality in temperate reservoirs, but high prey biomass may mitigate the negative effect of hypoxia.